Teaching of Research Methodology in Nursing History: evaluation of educational strategy for undergraduation students - Luciana Barizon Luchesi; Wellington Mendonça de Amorim; Fernando Porto (Universidade Federal do Estado do Rio de Janeiro, 2009)
The objective is to identify the impact of the use of a pedagogical strategy for teaching research methodology in the History of Nursing in a course designed for undergraduate students in Nursing. This is a descriptive, quantitative research, which had as source of data a self-administered questionnaire with closed and open questions and an essay prepared by nursing students at the end of the course about their perception of the importance of study History of Nursing during undergraduation course. Among the course participants 33.3% participated in the study. It was concluded that the course was successful in the evaluation of students, and it contributed for more mature professional, scientific and cultural development of the students, there was demonstration of internalization of concepts described in the scientific literature and also presented as impact the production of five micro research projects and consolidation of an interinstitutional laboratory of studies. Descriptors: Nursing, History of Nursing, Teaching.